Keputusan Pembelian Ditinjau dari Product Quality, Brand Image, Brand Trust pada Mahasiswa Pengguna Smartphone Oppo di Universitas Islam Batik Surakarta - Dewi Nur Wulan; Siti Maryam; Istiqomah Istiqomah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the influence of product quality, brand image, and brand trust on purchase decisions among student who use Oppo smartphone at Universitas Islam Batik Surakarta. This population consisted of active students at Univeritas Islam Batik Surakarta who use Oppo smartphones, with a total sample of 105 respondents. Data were collected using quentionnaires distrivuted trought a purposive sampling technique. Data analysis was conducted using multiple linear regression analysis, coefficient of determination (R2), F-test, and t-test. The results indicate that product quality, brand image, and brand trust have a positive and significant effect, both partially and simultaneously, on purchase decisions.